Analisis bullwhip effect dalam sistem rantai pasok pada produk Abon dan Dendeng Sapi Asri - Indra Kusumajati Susanto; RR. Rieka F Hutami (Operations Excellence: Journal of Applied Industrial Engineering, 2021)
One of the obstacles facing micro, small and medium-sized enterprises (MSMEs) in Indonesia is the bullwhip effect. The bullwhip effect is an event that occurs in the supply chain due to an increase in order fluctuations or order cancellations due to information distortions. This study aims to determine the value of the bullwhip effect and explain the main causes of its occurrence in order to explain about the approach to reducing the bullwhip effect in micro, small and medium-sized enterprises (MSMEs) in Indonesia that operational management can be maximized through operational management. This study uses quantitative methods to determine the value of the bullwhip effect. And qualitative methods are used to identify the root cause and reduction of the bullwhip effect. With primary data from interviews. In addition, secondary data comes from demand data and order data on products for distributors and retailers managed by the company. The results showed that the value of the bullwhip effect on the product at one of the micro, small and medium-sized enterprises (MSMEs) in Indonesia was almost completely above 1.00 and above the specified parameters. This provides information that there is a product bullwhip effect in one of the micro, small and medium-sized enterprises (MSMEs) in Indonesia. Meanwhile, the main cause of the bullwhip effect in one of the smallest, small and medium-sized enterprises (MSMEs) in Indonesia is a demand forecast error.